Motivational Pathways to Primary Islamic Teacher Education: Toward an Integrative Model - Umi Lailatul Putri; Baharudin; Muhammad Muchsin Afriyadi (Al'Adalah, 2025)
This article examines students’ motivational pathways in choosing the Islamic Primary School Teacher Education Programme and proposes an Integrative Motivation Pathway Model for prospective Islamic primary teachers. Using a descriptive qualitative design at UIN Raden Intan Lampung, primary data were collected through open-ended questionnaires administered to 150 first-year students and semi-structured interviews with 10 purposively selected students and the Programme Secretary. Data were analyzed following Miles and Huberman’s interactive model, supported by source and method triangulation. The findings show that internal motivational pathways are anchored in a combination of spiritual drive, professional interest in teaching, and aspirations for character-based self-development. Family support, programme image, a religious campus culture, lecturer influence, and perceived career prospects within Islamic educational institutions reinforce external pathways. Synthesising these pathways, the proposed model conceptualizes programme choice as an interlocking process in which spiritual, professional, and social dimensions converge from initial intention to sustained career commitment. The model extends the application of Maslow’s and Herzberg’s motivational frameworks within Islamic teacher education, offering practical implications for program governance and student motivation development.